Kamgar Sadan building - Mumbai Archive Project Team (Jio Institute, 2024)
Saraswati Nakhva received her education at the Nawab Tank Upper Primary Municipal Marathi School, located inside the Kamgar Sadan building. This building was established by the Port Trust of India in 1937, and it is located in the Railway Colony at Mazagaon Koliwada.